Pengembangan Media Kritik dan Saran Universitas Pendidikan Ganesha Berbasis Android Mobile - Putu Maha Putra; I Made Gede Sunarya; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2013)
This is a research and development study which aimed to design and implementation of media criticism and suggestions based on android mobile. The method used in the implementation of media criticism and suggestions are android based mobile in its design and the waterfall method using DFD (Data Flow Diagram) with two entities, namely administrators, and users. Media consists of 9 main processes are the main sign in process, user data processing, status and wall post data processing, message data processing, comment data processing, add friends, notifications, like and sign out. Implementation of media criticism and suggestions produced an android based mobile software that can be a medium for students to present criticisms and suggestions to be conveyed to the Undiksha and environment faculty of Undiksha. Media criticism and suggestions produced an android based mobile is a web-based application for administrators and users as well as applications for android users. Media criticism and suggestions in the implementation process of using Adobe Dreamweaver CS3 as a text editor on creating web-based applications and the applications built using eclipse juno android, Java JDK7, Rev.20 SDK, ADT and built for devices with minimum android version 2.3 (API 10 ) for the implementation of database use MySQL.